STRATEGI OPTIMALISASI PERANAN POLISI KEHUTANAN DALAM MENANGGULANGI ILLEGAL LOGGING DI KAWASAN TAMAN NASIONAL GUNUNG PALUNG - Rochdat, Cucu; Nurdjali, Bachrun; Oki W, Ganjar (Universitas Tanjungpura, 2013)
TNGP forest ranger has made efforts in combating illegal logging, yet there still found any illegal logging that activity. This study aims to identify environmental conditions inside (internal) and outside (external) on the countermeasure illegal logging by TNGP forest ranger, and find alternative strategy which concerns the prevention of illegal logging by TNGP forest ranger. Methods used is observation with interview assisted guide interview. Primary data is sourced from the 17 respondents sample of 11 research object as a purposive sampling. Results of the study and analyze issues or alternative strategies do with SWOT analysis, IFE and EFE were then formulated with SWOT matrix. Research internal, strength factor with the highest weighting, namely the existence of a strategy for tackling illegal logging was done by TNGP forest ranger. A factor of weakness namely forest ranger not comparable to TNGP space. External identification, opportunities factor with the highest weighting namely having authority full given ministry of forestry in addressing all cases criminal act forestry happened in TNGP area. The threat factor is the factors are interest to develop its territory governments. An alternative strategy found that is optimize and increase the capability of forest ranger , maximize of facilities infrastructures and utilizing obtain additional from NGO, illegal logging preventife improvement program based on the authority of forest ranger, maintain and develop the program handling the illegal logging that already exist, maximize the participation of indigenous people, and integrating all components related stakeholders through the opportunities of Presidential Instruction No. 4/2005. Keywords: Strategy, Forest Ranger, Illegal Logging.